2012
DOI: 10.7314/apjcp.2012.13.9.4597
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Toxicity, and Anticancer Activity of Zingiber Officinale Roscoe Against Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is an uncommon adenocarcinoma which arises from the epithelial cells of the bile ducts. The aim of the study was to investigate the cytotoxicity, toxicity, and anticancer activity of a crude ethanolic extract of ginger (Zingiber officinale Roscoe) against CCA. Cytotoxic activity against a CCA cell line (CL-6) was assessed by calcein-AM and Hoechst 33342 assays and anti-oxidant activity was evaluated using the DPPH assay. Investigation of apoptotic activity was performed by DNA fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…Therefore, kidney cells were used in the study. Limited genotoxicity data were available for the herbs included in this study, with the exception of data from a small number of prior studies conducted to assess their antimutagenic/anticarcinogenic potentials (49)(50)(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, kidney cells were used in the study. Limited genotoxicity data were available for the herbs included in this study, with the exception of data from a small number of prior studies conducted to assess their antimutagenic/anticarcinogenic potentials (49)(50)(51)(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…DC., Zingiber officinale Roscoe and Piper chaba Hunt. (Mahavorasirikul et al ., ; Na‐Bangchang and Karbwang, ; Plengsuriyakarn et al ., ; Plengsuriyakarn et al ., ). Herbal medicines are mixtures of more than one active ingredient, and therefore, the likelihood of drug–herb interaction is theoretically higher than drug–drug interaction as synthetic drugs usually contain single chemical entities.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, MDR1 and MRP3 may be involved in conferring resistance of CCA to ginger extract [17]. Result showed that ethanolic extract produced remarkable reduction in number of viable cells (p < 0.01) and increased the percentage of life span.…”
Section: Premanathan Et Al (2012)mentioning
confidence: 97%